2011
DOI: 10.1007/s00344-011-9222-z
|View full text |Cite
|
Sign up to set email alerts
|

Sugar and Light Effects on the Condition of the Photosynthetic Apparatus of Arabidopsis thaliana Cultured in vitro

Abstract: Light and sugars are fundamental elements of plant metabolism and play signaling roles in many processes. They are also critical factors determining the condition of plants cultured in vitro. The aim of this work was to investigate the simultaneous influence of irradiance and sugar content in the medium on the growth and photosynthetic apparatus condition of Arabidopsis thaliana in vitro. Plants were grown on media containing 1 or 3% of sucrose or glucose at three irradiances: 25, 100, and 250 lmol m-2 s-1 (we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
1
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(58 citation statements)
references
References 33 publications
(19 reference statements)
1
52
1
3
Order By: Relevance
“…The lower pigment accumulation observed in tissues from the culture media supplemented with 30 g L -1 sucrose and NAA, regardless the closure type, is a typical response found in the literature, being attributed to the effects of sucrose on biosynthesis of photosynthetic pigments, which result in inhibition of chlorophyll biosynthesis and in vitro photosynthesis (Eckstein et al, 2012). Plantlets grown without sucrose show a higher photosynthetic rate because this is the only route to carbon fixation (Iarema et al, 2012).…”
Section: Discussionmentioning
confidence: 61%
“…The lower pigment accumulation observed in tissues from the culture media supplemented with 30 g L -1 sucrose and NAA, regardless the closure type, is a typical response found in the literature, being attributed to the effects of sucrose on biosynthesis of photosynthetic pigments, which result in inhibition of chlorophyll biosynthesis and in vitro photosynthesis (Eckstein et al, 2012). Plantlets grown without sucrose show a higher photosynthetic rate because this is the only route to carbon fixation (Iarema et al, 2012).…”
Section: Discussionmentioning
confidence: 61%
“…Therefore we can infer that the absence of nutrients combined with genetic factors may cause higher rates of abnormal plants. When cultivating Arabidopsis thaliana using different concentrations of sugar, ECKSTEIN et al (2012) observed that plants cultivated without this carbohydrate were slower to develop and did not reach the generative phase. Some species do not depend on nutritive medium, for example the genipap, which showed a higher rate of germination and formation of normal seedlings when cultivated without salts and sucrose (ALMEIDA et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…The effects of sugars on plant aquaporins (and water conductance) have recently been examined; it was observed that glucose reduces the movement of water from the xylem to the mesophyll [41], which could also affect leaf growth. It has also been shown that sugars (such as, glucose and sucrose) can affect the movement of cellular organelles, including chloroplasts [42,43]. Trehalose (at a concentration about 25 mM) inhibited root elongation in A. thaliana seedlings, whereas sucrose did not affect this process [44].…”
Section: Introductionmentioning
confidence: 99%